PERTUMBUHAN KELAPA SAWIT (Elais guineensis Jaqc. ) DI PEMBIBITAN UTAMA DENGAN PERBEDAAN KOMBINASI PUPUK CAIR NUTRIFARM DAN NPKMg (The Seedling Growth Of Oil Palm (Elais guineensis Jaqc) In Nursery With Different Liquid Fertilizers Nutrifarm And NPKMg Comb - . Gusniwati; Helmi Salim; Juwita Mandasari (Bioplantae, 2012)
This experiment was conducted to determine the growth of oil palm seedlings to the provision of a complementary combination liquid fertilizer and manure Nutrifarm AG and NPKMg recommendations. This study was conducted at Agriculture Farm Faculty of Agriculture, University of Jambi. This research arranged with Randomized Block Design (RBD) with 6 treatment. Without liquid fertilizer supplement Nutrifarm AG 5 ml.L-1 with 100% NPKMg fertilizer recommendations (control), liquid fertilizer supplement Nutrifarm AG 5 ml.L-1 with no NPKMg, Nutrifarm AG 5 ml.L-1 with 25% water NPKMg, Nutrifarm AG 5 ml.L-1 with 50% water NPKMg Nutrifarm AG 5 ml. L-1 with a 75% water NPKMg, Nutrifarm AG 5 ml.L-1 with 100% water NPKMg. Parameter variables number of leaves, total leaf area, seed diameter, plant dry weight, root dry weight. The data were statistically analyzed and followed by Duncan Multiple Test A (DNMRT) at the level of 5%. Results showed combination liquid fertilizer and manure Nutrifarm AG NPKMg recommendation responds to the high seedling growth, total leaf area and diameter of the seed. And efficient use good combination is the provision of a complementary combination liquid fertilizer Nutrifarm AG 5 ml.L-1 water with 25% fertilizer NPKMg recommendation on oil palm seedlings in the main nursery.Key words : Oil Palm, nutrifarm